Optimization of East Pier Operational Services PT. Pelabuhan Indonesia (Persero) Benoa Branch - Ramadan, Agus Cipto Gilang; Priyono, Budi; Nasihah, Ainun (Universitas Hang Tuah, 2025)
As one of the transportation infrastructures, the port has a strategic role to support the transportation system because it is a node point of connection between regions/countries. The human resources of Benoa port in the operational field are not balanced with the infrastructure, due to the lack of skill development in the use of embarkation and debarkation equipment. The operational service process requires improvement to reduce ship waiting time. A data collection must be supported by appropriate techniques and accompanied by systematic implementation, to obtain more complete, objective, and accountable data. Research with the title “Optimization of Operational Services at the East Pier of PT. Pelabuhan Indonesia (Persero) Benoa Branch” resulted in the discovery of difficulties related to the services provided by Benoa Port human resources and the availability of escort facilities at the port. With the current operational conditions of the port, the international terminal operational service procedures related to HR arrangements at Benoa Port are in accordance with operational needs in the executive and functional fields for domestic services. The existing supporting equipment is also adequate for international cruise ship services.